Female cuckoo calls elicit vigilance and escape responses from wild free-range chickens. Issue 1 (2nd January 2021) - Jiang, Xingyi; Zhang, Changjie; Liu, Jianping; Liang, Wei
Abstract : Mimicry is widespread in the animal kingdom. Parasitic cuckoos can reduce the risk of their offspring being rejected by employing morphological and egg mimicry. Female common cuckoos ( Cuculus canorus ) can deceive their hosts by mimicking sparrowhawk ( Accipiter nisus ) calls, thus improving brood parasitism success. However, few experiments have confirmed the hypothesis that female cuckoos can successfully mimic sparrowhawk calls. We used two populations of wild free-range chickens ( Gallus gallus domesticus ), which are not cuckoo hosts, to study the effects of four different types of bird calls on their anti-predatory behavior. Results showed that both female cuckoo and sparrowhawk calls elicited vigilance and escape responses from chickens, while the chickens did not respond to either male common cuckoo or Oriental turtle dove ( Streptopelia orientalis ) calls. This suggests that female cuckoo calls can not only deceive their hosts, but also successfully deceive their non-host birds. Our study further confirms the accuracy with which female cuckoos can mimic sparrowhawk calls.